2019
DOI: 10.1016/j.renene.2018.10.095
|View full text |Cite
|
Sign up to set email alerts
|

Using lakes and rivers for extraction and disposal of heat: Estimate of regional potentials

Abstract: Using lakes and rivers for extraction and disposal of heat: estimate of regional potentials. Renewable Energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Analysis of the data and comparison with both radiometric and in situ observations at Buchillon showed that quality flags are not a sufficient measure to reliably quantify the accuracy of the AVHRR images but to improve the quality, avoiding errors (e.g., cloudcontaminated pixels). Indeed, we observed strong fluctuations of up to ±3 • C between skin and bulk temperature, especially during daytime when a micro-stratification establishes in the surface layer (Gentemann et al, 2003). Skin and bulk temperature becomes similar under windy or convective conditions.…”
mentioning
confidence: 76%
“…Analysis of the data and comparison with both radiometric and in situ observations at Buchillon showed that quality flags are not a sufficient measure to reliably quantify the accuracy of the AVHRR images but to improve the quality, avoiding errors (e.g., cloudcontaminated pixels). Indeed, we observed strong fluctuations of up to ±3 • C between skin and bulk temperature, especially during daytime when a micro-stratification establishes in the surface layer (Gentemann et al, 2003). Skin and bulk temperature becomes similar under windy or convective conditions.…”
mentioning
confidence: 76%
“…Both the warming trend and the increase in length of the stratified period increase the Schmid stability ( Figure 4e) and heat content ( Figure 4f). The increase of Lake Brienz heat content amounts to ~2•10 16 J over 38 years, which corresponds to roughly two thirds of the heat extraction potential for this lake (Gaudard et al, 2019). Contrarily to the above-described variables, no clear trend was detectable in the yearly maximum stratification strength (Brunt-Väisälä frequency, Figure 4d).…”
Section: Long-term Evolution Of the Thermal Structure Of Lakes Respomentioning
confidence: 91%
“…The Darcy friction factor (f D ) in Equation (1) can be obtained from the Reynolds number and the surface roughness (e) divided by the hydraulic pipe diameter (d) shown in Equations (4)- (6), which is known as the Churchill relation [29]. (6) where Re (-) is the Reynolds number, which is a function of the fluid properties as follows,…”
Section: Of 16mentioning
confidence: 99%
“…However, it has a burden of legislative permits and costs for lake water extraction and returning and risks of freezing, corrosion, and biofouling, which can obstruct the stable operation of the system [2][3][4][5]. In particular, the discharge of water used for the operation of the open-loop system can affect the physical properties and the ecological conditions of lakes [2,5,6]. Comparing the open-loop system to the closed-loop LWHP system may have relatively low efficiency and a concern for leakage of a heat-carrier fluid due to accidental pipe failure [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation